2019
DOI: 10.1371/journal.pone.0222204
|View full text |Cite
|
Sign up to set email alerts
|

Reasons behind stymied public hospital governance reform in China

Abstract: BackgroundThe public hospital governance reform in China is pledged to improve the governance of public hospitals and deliver affordable and high-quality care. However, progress in public hospital reform has been slow. The reason is poorly understood.MethodsA research center affiliated with China National Health Commission has conducted 32 workshops to interview 124 public hospital administrators from 30 provincial-level administrative divisions and 105 various-level government officials from three provinces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The studies confirmed that less than 7% of hospital managers possessed management related qualifications or receiving extensive management training [22]. These studies reinforce the urgent need to improve management efficiency in Chinese public hospitals by strengthening the management competence of hospital managers in the areas of leadership and decision-making [24].…”
Section: Introductionmentioning
confidence: 53%
“…The studies confirmed that less than 7% of hospital managers possessed management related qualifications or receiving extensive management training [22]. These studies reinforce the urgent need to improve management efficiency in Chinese public hospitals by strengthening the management competence of hospital managers in the areas of leadership and decision-making [24].…”
Section: Introductionmentioning
confidence: 53%
“…A brief search of literature from year 2000 onwards has found only15 studies focussing on the management capacity and competency of managers in Chinese public hospitals [23]. The studies confirmed that less than 7% of hospital managers possessed management related qualifications or receiving extensive management training [22]. These studies reinforce the urgent need to improve management efficiency in Chinese public hospitals by strengthening the management competence of hospital managers in the areas of leadership and decision-making [24].…”
Section: Introductionmentioning
confidence: 91%
“…Firstly, there are no agreed management standards and requirements currently used to guide hospital managers recruitment other than seniority and clinical performance [21]. Hence, the absence of a management track record [22] and the lack of specific management training among managers prior to taking up management positions is common in public hospitals in China [21]. Secondly, most postgraduate training is non-management and research focused rather than coursework-based / practice-based unlike many Master of Health Administration coursework programs offered by universities in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, patient-provider relationships in China appeared to deteriorate after economic and healthcare reforms in the 1980s [ 3 , 13 , 14 ]. The current healthcare system faces challenges in delivering affordable and quality care with an acceptable bedside manner [ 15 , 16 ]. Ironically, the public-hospital-centered health system is mostly profit-driven [ 15 ].…”
Section: Introductionmentioning
confidence: 99%